Viscoelastic properties of a thioether-based heliconical twist–bend nematogen. Issue 17 (23rd April 2020) - Zhou, Junchen; Tang, Wentao; Arakawa, Yuki; Tsuji, Hideto; Aya, Satoshi
Abstract : The manuscript presents quantitative measurements on fundamental viscoelastic properties in the twist–bend nematic phase as well as in the nematic phase, formed by achiral molecules. Abstract : The twist–bend nematic (NTB ) phase is one of the new types of nematics found recently, which possesses local nematic order with a heliconical orientational modulation at the nanoscale. Herein, we quantitatively determined, for the first time, the temperature-dependent elastic and viscosity properties in both the nematic (N) and NTB phases using a thioether-linked cyanobiphenyl dimer CBS7SCB exhibiting a broad temperature range of the NTB phase which is stable down to room temperature. In the N phase, the fundamental elastic moduli: splay and bend elastic moduli ( K 11 and K 33, respectively) are found to be in the order of 10 −12 N, and the effective rotational viscosity ( γ 1 ) is determined to be in the range of 5–200 mPa s. Meanwhile, the NTB phase is found to exhibit a compressive elastic modulus B in the order of several tens of kilopascals, the effective K 11 in the order of 10 −10 –10 −8 N, and a considerably large γ 1 value of ∼68.7 Pa s right below the N–NTB phase transition. The present study provides insights into the comprehensive viscoelastic properties based on comparison of the obtained experimental data with not only the existing theoretical prediction but also the preceding experimental works.